RICH BRIAN’S RESISTANCE AGAINST RACISM IN INSTAGRAM - Syamsi, Ekaprilia Mutiara; Chusna, Aidatul; Trisnawati, Ririn Kurnia (CALL, 2024)
Racism can trigger the development of an individual's resistance due to the inequality between ethnic minority and majority groups. This study aimed to discover the forms of resistance shown by Rich Brian through his Instagram account. The method used in this research is descriptive qualitative method by applying the resistance theory by Ellefsen, Banafsheh, and Sandberg (2022). The data source used in this research comes from Rich Brian's Instagram account with the username @brianimanuel (https://www.instagram.com/brianimanuel/). The data used in this study are verbal and visual components of Rich Brian’s Instagram posts. The results of the analysis show that the emergence of Rich Brian's resistance against racism occur after he experiences various forms of racism while being part of an ethnic minority in the United States. Rich Brian's Instagram account only displays four of the five resistance forms identified in Ellefsen et al.'s framework: ignoring, confronting, protesting, and sharing experiences. Keyword: racism, resistance, ethnic, instagram, social media